Dynamic Behavior of Pb(II) and Cr(III) Biosorption onto Dead Anaerobic Biomass in Fixed-Bed Column, Single and Binary Systems (Journal of Engineering, 2014)
The biosorption of lead (II) and chromium (III) onto dead anaerobic biomass (DAB) in single and binary systems has been studied using fixed bed adsorber. A general rate multi- component model (GRM) has been utilized to predict the fixed bed breakthrough curves for single and dual- component system. This model considers both external and internal mass transfer resistances as well as axial dispersion with non-liner multi-component isotherm (Langmuir model). The effects of important parameters, such as flow rate, initial concentration and bed height on the behavior of breakthrough curves have been studied. The equilibrium isotherm model parameters such as maximum uptake capacities for lead (II) and chromium (III) were found to be 35.12 and 23.84 mg g-1 respectively. While pore diffusion coefficients (Dp) were obtained to be 7.23×10-11 and 3.15×10-11 m2 s-1 for lead (II) and chromium (III) respectively from batch experiments. The results show that the general rate model was found correct for describing the biosorption process of the dynamic behavior of the DAB adsorber column.